Circulating tumor cell clusters-associated gene plakoglobin is a significant prognostic predictor in patients with breast cancer - Wataru Goto; Shinichiro Kashiwagi; Yuka Asano; Koji Takada; Katsuyuki Takahashi; Takaharu Hatano; Tsutomu Takashima; Shuhei Tomita; Hisashi Motomura; Masahiko Ohsawa; Kosei Hirakawa; Masaichi Ohira (BMC, 2017)
Abstract Background Circulating tumor cells (CTCs) are linked to metastatic relapse and are regarded as a prognostic marker for human cancer. High expression of plakoglobin, a cell adhesion protein, within the primary tumor is positively associated with CTC clusters in breast cancer. In this study, we investigated the correlation between plakoglobin expression and survival of breast cancer. Methods We evaluated 121 breast cancer patients treated with neoadjuvant chemotherapy. Expression of plakoglobin was identified by immunohistochemical staining in the cell membrane. We also examined the relation between the expression of plakoglobin and E-cadherin, an epithelial-mesenchymal transition (EMT) marker. Results Patients with high plakoglobin expression had significantly worse distant-metastasis-free survival (DMFS) (P = 0.016, log rank). Plakoglobin expression had no correlation with pathological complete response rate (P = 0.627). On univariate analysis with respect to distant metastasis, high plakoglobin expression showed worse prognosis than low plakoglobin expression [P = 0.036, hazard ratio (HR) = 3.719]. Multivariate analysis found the same result (P = 0.013, HR = 5.052). In addition, there was a significant relationship between the expression of plakoglobin and E-cadherin (P = 0.023). Conclusions Plakoglobin expression is an independent prognostic factor in patients with breast cancer, particularly for DMFS, and this is related to EMT.